Metacognitive Awareness in University Graduates in Engineering, Architecture and Aeronautical Sciences - Arias Barahona G., Rosario (2020)
The objective of this research was to analyze the differences in metacognitive awareness and its dimensions at the beginning and end of the academic semester in a group of 96 students in the first cycle of engineering, architecture and aeronautical sciences at a private university in Lima. We also seek to establish differences in metacognitive awareness in terms of gender and the existence of a significant relationship between metacognitive awareness and its dimensions with academic performance. This was measured through the final average grades obtained in all subjects by students at the end of the semester. It makes use of a type of pre-test design -subsequent testing of a single group. This was measured through the final average grades obtained in all disciplines by students at the end of the semester. The instrument used for the evaluation was the Metacognitive Consciousness Inventory of Schraw and Dennison (1994) adapted in Peru by Córdova and García (2011).The results found a significant and favorable change in the metacognitive awareness and in its dimensions of planning and self-regulation in the post test; no significant relationships were established with gender or with academic performance.